Biotic integrity of the Mar Muerto lagoon, Mexico, based on fish - Monzón Hernández, Luis Edson; Peralta Meixueiro, Miguel Ángel; Aguilar Ballina, José Manuel; Rivera Velázquez, Gustavo; Vega Cendejas, María Eugenia (Revista de Biología Tropical, 2024)
Introduction: The Mar Muerto lagoon is an ecosystem characterized by high productivity upon which various inhabiting organisms depend. Additionally, it is a system susceptible to environmental impacts. Consequently, indices have been developed to determine the degree of disturbance caused by natural and/or anthropogenic factors. Objective: To assess the degree of disturbance in the Mar Muerto lagoon using a Biotic Integrity Index (BII) based on ichthyofauna. Methods: From December 2019 to March 2021, 12 sampling stations were established in the lagoon. The Biotic Integrity Index was developed by collecting data on hydrological variables (salinity, dissolved oxygen, pH, electrical conductivity, suspended solids, temperature, nitrites, nitrates, phosphates, and transparency) and classifying fish species based on their composition and richness. This was followed by a Water and Habitat Quality Index (WHQI) derived from the characterization and classification of sampling stations based on physicochemical variables. The correlation of the two indices allowed for the evaluation of the effectiveness of the BII. Results: 65 species were reported for the lagoon, with Lile gracilis, Oligoplites altus, Eucinostomus currani, and Gerres simillimus being the most frequently recorded. Only station 10 exhibited poor biotic integrity (BII = 26), while the rest displayed regular biotic integrity (BII = 30 – 44), with station nine presenting the highest calculated value (BII = 42). The assessment of the lagoon’s BII demonstrated an average biotic integrity considered "regular." Conclusion: Through this study, the functionality of the modified BII for the Mar Muerto lagoon was verified, allowing for the evaluation of the present conservation status and comparison with previous studies.